Isolation and characterization of a Saccharomyces cerevisiae mutant with impaired glutamate synthase activity. - Folch, J L (1989)
A mutant of Saccharomyces cerevisiae that lacks glutamate synthase (GOGAT) activity has been isolated. This mutant was obtained after chemical mutagenesis of a NADP-glutamate dehydrogenase-less mutant strain. The gdh gus mutant is a glutamate auxotroph. The genetic analysis of the gus mutant showed that the GOGAT-less phenotype is due to the presence of two loosely linked mutations. Evidence is presented which suggests the possibility that S. cerevisiae has two GOGAT activities, designated GOGAT A and GOGAT B. These activities can be distinguished by their pH optima and by their regulation by glutamate. Furthermore, one of the mutations responsible for the GOGAT-less phenotype affected GOGAT A activity, while the other mutation affected GOGAT B activity.